Building PDA databases for wireless and mobile development - Laberge, Robert (Wiley Pub., 2003)
Introduces the mobile databases (their architecture and features) and how they operate and handle the essential task of synchronization. * Explains how the enterprise work force can move to a handheld device and still have easy access to corporate databases. * Web site contains all source code for working examples of applications showing mobile databases in use. * Foreword and endorsement by Bill Inmon, the "Father of Data Warehousing."